Islam as an Environmentally Friendly Religion: Critical Analysis of the Ecological Politics in the Establishment of a Cement Factory in Rembang, Indonesia - Muhammad Solikhudin (Indonesian Academy of Social and Religious Research (IASRR), 2020)
Boisterous problems occur in Indonesia and other parts of the world. The issue of Cement Plant in Rembang spread in online and offline media is an example that can be disclosed here. People around the cement factory in Rembang who work as farmers attempt to stop the practice by casting the foot together. The reason is that food security must be maintained, and natural beauty also needs to be maintained. This problem is still a tug-of-war among government, employers, and the people. Islam as a religion of compassion, certainly teaches a sense of justice and humanity to all humanity. In direct proportion to Islam, green political reasoning also likes this. In this paper will be parsed study Cement Plant Perspective Green Politics, as an effort to maintain the continuity of human life and care for the beauty of nature. In a country that embraces a democratic system and applies green political theory, it should implement three aspects, namely: First, distributing justice, Second, committed to democratization process, Third, Efforts to achieve ecological sustainability.